Cytotoxic Activity of Selected Zingiberaceae - L.R, Ling,; Wahab N, Abdul; Abidin N, Zainal (Malaysian Journal of Science, 2005)
Zingiberaceae is a well-known plant family in Southeast Asia that have been widely used as spices and for medicinal purposes throughout the world. In this preliminary study, crude petroleum ether, chloroform and methanol extracts obtained from ten selected Zingiberaceae were screened for possible cytotoxic activity against CaSki cells by using an in vitro neutral red cytotoxicity assay. The results demonstrated that all extracts tested showed cytotoxic effect on CaSki cells, a cervical cancer derived cell line. The trend observed was that the percentage of killing increased with the concentration of extracts tested. Fifteen extracts (50%) were found to be cytotoxic with ED₅₀ values equal to or less than 20 µg/ml. The petroleum ether extract of Languas galanga with an ED₅₀ value of 3.8 µg/ml, chloroform extract of Curcuma domestica with an ED₅₀ value of 2.0 µg/ml and methanol extract of Curcuma xanthorrhiza with an ED₅₀ value of 13.8 µg/ml were the most active extracts for each solvent used. Overall, petroleum ether and chloroform extracts of Zingiberaceae showed greater cytotoxic activity against CaSki cells compared to methanol extracts. However, the mechanism of action has not been investigated in the present study. Zingiberaceae species have great potential to be exploited for the search of novel anticancer agents for the future.